Neoconservatism and Foreign Policy: a comparative analysis between George W. Bush and Donald Trump's governments - Dall'Agnol, Gustavo Fornari (Faculdade de Filosofia e Ciências, 2021)
The present paper conducts a comparative analysis between George W. Bush and Donald Trump’s foreign policy in order to explain the differences and similarities of their foreign policy doctrine. To accomplish this goal, the study resorts to the state of the art of Foreign Policy Analysis and Foreign Policy Decision Making literature. The present paper argues that the constitution of domestic coalitions and the transformations of the International System satisfactorily explain, in general terms, the conduction a government’s Foreign Policy. George W. Bush’s government, sustained by a cohesive coalition, necessary for the implementation of a Foreign Policy doctrine, is best defined as neconservative in its international conduct. The present paper shows that there is no Trump doctrine. This fact is due to the difficulties that his government has in forming a coalition which would enable the necessary societal mobilization and resource extraction around a well-defined strategy. China’s rise and Russia’s return as main strategic competitors further deepens the country’s establishment dispute, which is divided between the strategies of engagement and restraint.